2016
DOI: 10.1007/s00264-016-3372-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of open and arthroscopic coracoid transfer for shoulder anterior instability (Latarjet)—clinical results at short term follow-up

Abstract: Results Average time of surgery was significantly shorter in ARTHRO than OPEN: respectively 110 and 120 minutes. The number of intra-operative complications was six (12.5%) in OPEN and five (8.1%) in ARTHRO. The results were comparable in both groups, with no significant difference between OPEN and ARTHRO group: satisfaction rate -96.8% and 91.9%, shoulder function -92.2% and 90%, Walch-Duplay score -83.9 and 76.7 respecively. A significant difference was reported in Rowe score: 87.8 in OPEN and 78.9 in ARTHRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…The authors point out that a tight sling in relative adduction may explain greater restriction of external rotation in adduction than abduction. Similar findings were reported by Kordasiewicz et al 3 In that study comparing 62 arthroscopic versus 48 open Latarjet procedures, although the rate of "recurrent instability" was similarly low (4.8% arthroscopic; 6.2% open), "subjective apprehension" was reported to be 50% for the arthroscopic and 28% for the open procedures. Inadequate sling tension related to the location of the subscapularis split and coracoid graft placement is a possible contribution to the persistent apprehension in half of the arthroscopic cases.…”
Section: See Related Article On Page 2120supporting
confidence: 86%
“…The authors point out that a tight sling in relative adduction may explain greater restriction of external rotation in adduction than abduction. Similar findings were reported by Kordasiewicz et al 3 In that study comparing 62 arthroscopic versus 48 open Latarjet procedures, although the rate of "recurrent instability" was similarly low (4.8% arthroscopic; 6.2% open), "subjective apprehension" was reported to be 50% for the arthroscopic and 28% for the open procedures. Inadequate sling tension related to the location of the subscapularis split and coracoid graft placement is a possible contribution to the persistent apprehension in half of the arthroscopic cases.…”
Section: See Related Article On Page 2120supporting
confidence: 86%
“…However one study found no difference in VAS pain scores once patients had reached 30 days post-operatively [ 14 ]. One study ( n = 286 arthroscopic, 104 open, p < 0.05) found significantly better post-operative Walch-Duplay scores in the arthroscopic group [ 15 ], whereas the other two studies (n = 28 arthroscopic, 36 open, p > 0.05; n = 62 arthroscopic, 48 open, p > 0.05) reporting post-operative Walch-Duplay scores did not [ 10 , 16 ]. Interestingly one study ( n = 99 arthroscopic, 85 open, p < 0.05) reported significantly better post-operative WOSI scores in the arthroscopic group [ 14 ], whereas another study ( n = 36 arthroscopic, 22 open, p = 0.03) found significantly better WOSI scores in the open group [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly one study ( n = 99 arthroscopic, 85 open, p < 0.05) reported significantly better post-operative WOSI scores in the arthroscopic group [ 14 ], whereas another study ( n = 36 arthroscopic, 22 open, p = 0.03) found significantly better WOSI scores in the open group [ 13 ]. Similarly, one study (n = 62 arthroscopic, 48 open, p < 0.05) found significantly better Rowe scores in the open group [ 16 ], one study ( n = 286 arthroscopic, 104 open, p < 0.05) found better Rowe scores in the arthroscopic group [ 14 ], and one study ( n = 44 arthroscopic, 46 open, p = 0.181) found no significant difference [ 17 ]. No studies found significant differences in ASES or Constant-Murley scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have compared the results of open and AL, finding equivalent outcomes between the two 53 59 60. The only study to date comparing open versus arthroscopic anatomic glenoid techniques compared immediate radiographic results 15.…”
Section: Discussionmentioning
confidence: 99%